Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
y=7/3x²-13/3x+2
Step-by-step explanation:
Determine the value of c:
y=ax²+bx+c
2=a(0)²+b(0)+c
2=c
Substitute (1,0) into the quadratic and create an equation with a and b:
y=ax²+bx+2
0=a(1)²+b(1)+2
0=a+b+2
-2=a+b
Do the same with (3,10) to get a second equation:
y=ax²+bx+2
10=a(3)²+b(3)+2
10=9a+3b+2
8=9a+3b
Set the two equations equal to each other and solve for a and b:
-2=a+b
8=9a+3b
Multiply first equation by 3 and eliminate b to find a:
-6=3a+3b
- (8=9a+3b)
_______
-14=-6a
14/6=a
7/3=a
Substitute 7/3=a into the first equation:
-2=7/3+b
-2-(7/3)=b
-13/3=b
Final equation:
y=7/3x²-13/3x+2
See the graph for a visual representation
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.